Moments of silence authenticity in the cultural expressions of the Iran-Iraq war, 1980-1988 - Khakpour, Arta; Khorrami, Mohammad Mehdi; Vatanabadi, Shouleh (New York University Press, 2016)
The Iran-Iraq War was the longest conventional war of the 20th century. Centering on novels, films, memoirs, and poster art that gave aesthetic expression to the Iran-Iraq War, the essays gathered in this volume present multiple perspectives on the war's most complex and underrepresented narratives.